Investigating and Analyzing the Symbols in Haft Khan-e Rostam - Mahmoud Aghakhani Bijani; Ishagh Toghiani; Mohsen Mohammadi Fesharaki (Matn/Pizhūhī-i Adabī, 2018)
Symbolism exists in the thoughts and dreams of various human races and leads man to a range of non-speech thinking. From the past, the Iranian people have paid special attention to Shahnameh and established a close relationship with it according to its texture. During the Safavid period, the narratives in the cafes described the stories of Shahnameh with Pardeh-Xani and arrangement of scenes for entertainment. This research examines and decoding symbols in the images of Haft khan-e Rostam in Ferdowsi's Shahnameh. Rostam passes the seven-step test to save Kay Kāvus and achieving the championship base. Each khan (step) is a symbol of Rostam's confrontation with the hidden creatures that confronts him with the difficulty of reaching perfection. Rostam faces in the first step with lion (a symbol of pride and evil force), in the second step with thirst and warmth (the symbol of power without shape and spirit, as well as its hidden and unknown motive), in the third step with dragons (the symbol of drought), in the fourth step with the witch's wife (the symbol of the negative Anima), in the fifth step with the Devil who named Aowlad (symbol of door guard), in the sixth step with Arjhang Dave (the symbol of the anti-heroic helper) and in the seventh step with the white demon (the symbol of death and his blood symbol of life). The purpose of this research is to analyze the symbols in the illustrated images related to Haft khan-e Rostam in Ferdowsi's Shahnameh. The method of this study is descriptive-analytical. The results of the research show that in all the pictures, the symbols in the story of Haft khan-e Rostam in Shahnameh are presented in the pictures and it has made meaningful the relationship between the image and the original text for the audience.